Evolution of the Puccinia coronata population in Argentina and identification of resistance genes useful in oat breeding programs - Dietz, Juan Ignacio; Da Silva, Laura Victoria; Simón, María Rosa; Campos, Pablo Eduardo (Springer, 2024)
Crown rust caused by Puccinia coronata f. sp. avenae (Pc), is the most widespread and damaging disease in oat worldwide, causing significant losses in grain yield and quality. This research documents the evolution of the Pc population in Argentina and evaluates the potential of crown rust race-specific resistance genes for use in practical breeding in this region. For this, the virulence of 166 isolates of Pc collected in different locations of Argentina were characterized on a set of 9 oat differentials carrying Pc resistance genes. In total, 31 different races were found. Changes in the race population during the 2014–2021 period were observed with Pc populations in 2019 and 2021 being more complex and having a higher virulence frequency. This suggests that the use of a few genes (Pc38, Pc39, Pc50, and Pc51) as basis for resistance to crown rust in the Argentinian germplasm has resulted in the continuous selection of Pc phenotypes with virulence to these genes. In this sense, our results showed an increase in the frequency of virulence on Pc38 and Pc51 from 2014 to 2019–2021, reaching virulence frequencies greater than 80%. Likewise, Pc39 and Pc50 also exhibited frequencies higher than 80% in 2019, showing significantly higher values determined in previous work carried out with populations of Pc in Argentina. There were no races virulent on Pc48, Pc52 and Pc64 among the isolates collected. Furthermore, our data confirmed the effectiveness of these three genes in field trials. Data provided here may be helpful in making decisions on resistance breeding strategies, such as the deployment of major single genes or more complex gene pyramids.